Climate-Induced Polar Motion: 1900–2100 - Kiani Shahvandi, Mostafa; id_orcid:0 000-0001-5705-7014; Soja, Benedikt; id_orcid:0 000-0002-7010-2147 (Wiley, 2025)
It has been demonstrated that the motion of the Earth's rotational pole with respect to the crust—termed polar motion—is increasingly influenced by barystatic processes, that is, continental-ocean mass redistribution due to melting of polar ice sheets, global glaciers, and variations in terrestrial water storage. However, how these processes might impact polar motion in the 21ˢᵗ century is not known. Here we investigate this problem under various climatic scenarios, namely, Representative Concentration Pathways (RCP) and Shared Socioeconomic Pathways. We show that the climate-induced polar motion is sensitive to the choice of climatic scenario; under the optimistic RCP2.6, the rotational pole might wander by ∼12 m with respect to 1900, whereas under the pessimistic RCP8.5 by more than twice as much (∼27 m). The most important contributor is the melting of polar ice sheets (Greenland and, to a lesser degree, Antarctica), followed by melting of global glaciers, and variations in terrestrial water storage. ISSN:0094-8276 ISSN:1944-8007